2016
DOI: 10.1177/0266242616641749
|View full text |Cite
|
Sign up to set email alerts
|

The implications of international entrepreneurial orientation, politicization, and hostility upon SME international performance

Abstract: This article investigates the relationship between international entrepreneurial orientation (IEO) and international performance taking into account the moderating effects of politicization in internationalization decisions and international hostility.Using data from 208 Greek international SMEs, we found that IEO is positively related to international performance. We also found that neither politicization nor international hostility separately have any moderating effects on this relationship.However, the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 97 publications
7
60
0
10
Order By: Relevance
“…Also, entrepreneurial orientation (EO) and its influence on firm export performance have received substantial attention in exports context (Chen et al, 2016). Because of the changes in the business environment due to dynamic nature of exports market, EO is gaining more importance due to significant effect on firm export performance and providing the sustainable competitive advantage (Thanos et al, 2016). EO can reform the production process, adopting innovation practices and new outlet for products, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Also, entrepreneurial orientation (EO) and its influence on firm export performance have received substantial attention in exports context (Chen et al, 2016). Because of the changes in the business environment due to dynamic nature of exports market, EO is gaining more importance due to significant effect on firm export performance and providing the sustainable competitive advantage (Thanos et al, 2016). EO can reform the production process, adopting innovation practices and new outlet for products, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has shown confusing conclusions in the relationship between entrepreneurial orientation and corporate performance. Although plenty of empirical results show that firms with a higher level of entrepreneurial orientation often perform better than their counterparts (Clercq et al 2010;Thanos et al 2016;Wiklund and Shepherd 2005;Zahra and Covin 2015), some researchers find no positive relationship. For example, Runyan et al (2008) point out the positive EO-performance relationship can be only confirmed in the growth stage rather than in later periods.…”
Section: Entrepreneurial Orientation and Corporate Performancementioning
confidence: 99%
“…With stronger inclinations towards innovativeness, risk-taking and proactiveness, companies tend to continuously improve managerial methods, update manufacturing technologies, take risks to launch new products and become first movers to achieve advantageous market positions (Hunt and Arnett 2006;Lee et al 2001;Wiklund and Shepherd 2005). Therefore, companies with stronger entrepreneurial orientations are more likely to act ahead of their competitors and outperform counterparts (Clercq et al 2010;Thanos et al 2016).…”
Section: The Intermediary Role Of Entrepreneurial Orientationmentioning
confidence: 99%
See 2 more Smart Citations